Model Averaging and Feedforward Temperature Control in an Oscillating Annealing Furnace. Issue 21 (2018) - Jadachowski, L.; Steinboeck, A.; Kugi, A.
Abstract: The impact of an oscillating motion on the temperature uniformity of a specimen in an experimental annealing furnace is analyzed. For the specimen temperature, three feedforward control strategies using dynamic optimization are developed and compared. The controllers provide reference signals to electrically powered infrared lamps to ensure optimal temperature trajectories. In the first controller design, no specimen oscillation is considered. This design uses an amplified adjustment of the steady-state power distribution obtained from static optimization. The second and the third controller are developed for an oscillating specimen. Both these controllers are designed on the basis of a dynamic optimization problem, where in addition to the amplification factor the constant power distribution serves as additional degree of freedom. While the second controller takes into account the oscillating motion directly, the last approach utilizes time averaging of the model equations. An evaluation of all controllers is carried out with an experimentally validated model. This analysis shows that the temperature uniformity can be significantly improved when the specimen oscillates.